Early detection of incident using Vehicular Ad-hoc Network - Singh, B. (Institute of Electrical and Electronics Engineers Inc., 2014)
Vehicular Ad-hoc Networks (VANET) is mainly discussed todeploy of ITS (Intelligent Transportation Systems) analysis and design solutions for safety, security and road traffic monitoring with better management. Through the vehicle information exchange to vehicles, road side units (RSU) and infrastructure nodes, Traffic Monitoring Center (TMC) can support incident detection monitoring and management. In this context, Early Detection of Incident (EDI) presents and discusses in this paper, a Vehicle-to-Vehicle (V2V) cooperative technique for detecting incident early using Incident Detection Node (IDN). EDI is experimented under small-scale highway based scenario using two cars equipped with on-board unit and one access point (AP). EDI is evaluated with measurement of received signal strength indication(RSSI) using network monitoring tool. The experimented results demonstrate average throughput, average signal strength, overall performance of AP in vehicle-to-roadside (V2R). EDI results demonstrate incident detection probabilities and capability to detect accurately. Â© 2014 IEEE.